2013
DOI: 10.1007/978-3-642-36632-1_1
|View full text |Cite
|
Sign up to set email alerts
|

mConcAppt – A Method for the Conception of Mobile Business Applications

Abstract: Mobile business applications (mobile business apps) bear huge potentials for increased work productivity, work comfort, and even sales if they are of high quality. Usability and user experience, in particular, are among the key quality attributes. The high quality requirements of mobile business apps require them to be thoroughly engineered. Unfortunately, today's software engineering approaches are often too heavy-weight to allow developing highquality mobile business apps in the context of mobile projects, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…It shows ensemble learning techniques are more suitable for the classification task. For the app implementation, we follow the process model of mConcAppt [25] concept of Mobile Software Engg. The App uses the server of Sesame [26] where all the data already been stored.…”
Section: Resultsmentioning
confidence: 99%
“…It shows ensemble learning techniques are more suitable for the classification task. For the app implementation, we follow the process model of mConcAppt [25] concept of Mobile Software Engg. The App uses the server of Sesame [26] where all the data already been stored.…”
Section: Resultsmentioning
confidence: 99%
“…The approach presented (MAInEEAC, mConcAppt and their interrelation) is based on best practices resulting from many projects in which we have designed interaction in collaboration with non-expert stakeholders, and is even supposed to enable semiexperts to design a well-conceived HCI. An example of the application of the approach in an actual project can be found in [5]. However, the approach is still evolving and work is in progress.…”
Section: Resultsmentioning
confidence: 99%
“…After having accomplished a huge number of software engineering projects with interaction design activities, we have found that these methods, where stakeholders can speak freely, lead to more relevant information than strict formal and restricted approaches. One of these methods is the mConcAppt method [2,3,5], which is a method for the user-centered conception of mobile business apps. In this chapter, we focus on the part of mConcAppt that is relevant for the construction of the HCI.…”
Section: A Non-formal Methods Based On Maineeacmentioning
confidence: 99%